Anxiolytics, sedatives and hypnotics. Issue 8 (August 2016) - Barends, Clemens; Absalom, Anthony
Abstract: Anxiolytics and sedatives are used in current anaesthetic practice for two main reasons: for anxiolysis before surgery and as adjuvants during anaesthesia. A wide choice of agents are available. Their safety profile is dependent on their pharmacokinetic and pharmacodynamic profiles, patient co-morbidity and the experience of the clinician using them. All sedative drugs have the potential to cause severe respiratory depression, and hence they should only be used with standard physiological cardiorespiratory monitoring. This is especially true of procedural sedation administered by non-anaesthetists in remote locations. Drugs used for anaesthesia vary in their pharmacology, but have broadly similar clinical effects. The choice of drug is usually a matter of individual preference, although pharmacokinetic and pharmacodynamic parameters do influence the selection of anaesthetic agents, especially in day case surgery. Most intravenous agents are thought to alter consciousness by an effect at the GABAA or NMDA receptors or both. Our understanding of the mechanisms of action of anaesthetic drugs is incomplete, not least because of a lack of understanding of consciousness. Several theories have been proposed over the last century, but none of them have managed to comprehensively elucidate the processes involved. There is now a sense of expectation that with the use of modern imaging techniques, anaesthetic drug action can be better understood, and that this may help in our understanding of consciousness and cognitive functions.